Comparative approaches on the shops metallurgists for the modern viniculture. The pioneer Antonio Baldé, Gil Miret and Carlos Berri in Mendoza - Pérez Romagnoli, Eduardo (Centro de Historia Argentina y Americana, 2007)
This paper proposes a comparison among the main characteristics of the two shops pioneer metallurgists in the production of instruments and equipment for wineries and industrial stills, in the beginnings of the modern viniculture in Mendoza . The Catalan partners Antonio Baldé and Gil Miret began in 1885 and the Italian Carlos Berri in 1888. A general panorama is presented on the equipment of the shops and the objects produced, the characteristics of the labor, the formation in metallurgy of the proprietors, the insert of the two firms in the region, a reference to other economic activities developed by the managers and some complementary questions.